Gender, sex and gossip in Ambridge : women in the Archers - Courage, Cara; Headlam, Nicola (Emerald Publishing Limited, 2019)
The intrepid team of researchers who brought you Custard, Culverts and Cake: Academics on Life in The Archers return with a hard-hitting exposé on the lives of the women of Ambridge. In this new book, the Archers Academics are joined by former The Archers editor, Alison Hindell and real-life Academic Archer Dr Charlotte Connor (a.k.a. Susan Carter), to examine the power of gossip in Ambridge, portrayals of love, marriage, and motherhood, female education and career expectations, women's mental health and the hard-won right of women to play cricket.Gender, Sex and Gossip in Ambridge gives the reader a deeper understanding of the real life issues covered in the programme, an insight into the residents of Ambridge, and validation that hours of listening to The Archers is, in fact, academic research.
Includes indexes.
Keywords: Archers (Radio program); Radio programs -- Great Britain -- Criticism and interpretation.; Social Science -- Popular Culture.; Popular culture.; elektronické knihy; electronic books